Morphological characterization of bacteria isolated from surfaces at the "Dr. César Guerra", central blood bank of Tucumán - D'arpino, María Cecilia (2022)
The microbiomes within the health care field play an important role as reservoirs of infectious diseases. Our goal was to study microbial communities at the Central Blood Bank. The surfaces from the Production and Molecular Biology Services underwent the processes of swabbing and growing in plates (LB pH7). The identification of the isolated strains was carried out through MALDI-TOF, and the morphological characterization was executed by means of Scanning Electron Microscopy (SEM). The species obtained are of clinical importance: as opportunist pathogens (Staphylococcus haemolyticus, Staphylococcus warneri, Clostridium subterminale, Brevibacterium casei, Staphylococcus saprophyticus), multiresistance to antibiotics (Staphylococcus cohnii ssp cohnii), formation of spores (Bacillus cereus group, Bacillus sp), or responsible for serious infections related to biofilms (Micrococcus luteus, Burkholderia cenocepacia, Pseudomonas stutzeri). Some isolated bacteria are of significance to bioremediation (Dietzia cinnamea, Dietzia maris, Bacillus subtilis/amyloliquefaciens/vallismortis, Pseudomonas stutzeri; Bacillus altitudinis/pumilus), and production of enzymes (Bacillus megaterium). The analysis of some strains with SEM revealed the presence of tubular structures, possibly nanotubes, associated to the production of biofilms and resistance to antimicrobials. Our findings show the bacterial diversity predominant at the blood bank, and describe the structures possibly involved in mechanisms of pathogenicity.